Potato Tuberworm Phthorimaea operculella (Zeller) (Lepidoptera: Gelechiidae) - Harsimran K. Gill; Gurminder Chahil; Gaurav Goyal; Arshdeep Gill; Jennifer L. Gillett-Kaufman (EDIS, 2014)
This document provides an overview of the potato tuberworm (Phthorimaea operculella), a pest affecting crops in the Solanaceae family, including potatoes, tomatoes, and tobacco. It discusses the pest’s distribution, life cycle, and the damage it causes to crops. The document also covers monitoring and management strategies, including cultural, biological, and chemical controls, as well as the importance of integrated pest management (IPM) programs. The goal is to provide comprehensive information to help manage and mitigate the impact of this pest on agricultural production.